2016
DOI: 10.5507/ag.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

Is pedometer-determined day-of-the-week variability of step counts related to age and BMI in Czech men and women aged 50 to 70 years?

Abstract: commonly reported activity in leisure time and a main part of active transportation activities provides possibilities for public health initiatives in mainly adult and senior populations (Pelclová, 2015). However, walking day-today variability appears not to be random. Volume of steps/day depends on gender and may fluctuate by day of week (weekdays-weekends), type of day (workdays-non-workdays), and by sport/exercise participation (Tudor-Locke et al., 2004). Extensive evidence in studies on children indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, the most recent data are included. On the basis of previous findings about the existing day-of-the-week variability of step counts per day in the Czech population ≤64 years with Sunday as the least-active day [39], seven days of data collection were chosen to more realistically estimate habitual volume of physical activity. This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the most recent data are included. On the basis of previous findings about the existing day-of-the-week variability of step counts per day in the Czech population ≤64 years with Sunday as the least-active day [39], seven days of data collection were chosen to more realistically estimate habitual volume of physical activity. This study has limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In the aging population, individuals with normal BMI achieve significantly more steps/day than individuals with overweight and obesity. Weekend days (especially Sunday) were the days with the lowest number of steps in men and women aged ≥50 years with overweight and obesity [56]. Present results indicated an association between increased BMI and decreased QoL in almost all domains (except environmental) of the WHOQoL-BREF.…”
Section: Discussionmentioning
confidence: 52%
“…Past research has demonstrated that behavioral differences between weekdays and weekends have a significant impact on health-related and dietary decisions. In particular, studies have found a common pattern of increased caloric intake and decreased physical activity on the weekend as compared with weekdays [1][2][3][4]. This circaseptan periodicity is not only limited to consumption but also seems to affect information-seeking behaviors.…”
Section: Weekly Patterns In General Health-related Behaviorsmentioning
confidence: 99%